Symmetric and asymmetric membranes based on La0.5Sr0.5Fe0.7Ga0.3O3-δ perovskite with high oxygen semipermeation flux performances and identification of the rate-determining step of oxygen transport. Issue 13 (October 2021) - Deronzier, E.; Chartier, T.; Geffroy, P.-M.
Highlights: The rate-determining step of oxygen transport depends strongly on the membrane architecture. Gaseous oxygen diffusion through thick porous support is the rate-determining step of oxygen transport. The asymmetric membrane architecture with a thin porous layer produced in this study achieves very high semipermeation fluxes. Abstract: This work focuses on identifying the rate-determining step of oxygen transport through La0.5 Sr0.5 Fe0.7 Ga0.3 O3- δ membranes with symmetric and asymmetric architectures. The best oxygen semipermeation fluxes are 3.4 10 −3 mol. m -2 .s -1 and 6.3 10 −3 mol. m -2 .s -1 at 900 °C for the symmetric membrane and asymmetric membrane with a modified surface. The asymmetric membrane with a modified surface leads to an increase of approximately 7 times the oxygen flux compared to that obtained with the La0.5 Sr0.5 Fe0.7 Ga0.3 O3- δ dense membrane without surface modification. This work also shows that the oxygen flux is mainly governed by gaseous oxygen diffusion through the porous support of asymmetric La0.5 Sr0.5 Fe0.7 Ga0.3 O3- δ membranes.